PENENTUAN ZONASI POLA PEWADAHAN DAN PENGUMPULAN SAMPAH PADA KAWASAN GUNUNG TRAKTOR - Muhammad Yurda; Rahmi Yorika (Arsitektur Universitas Muhammadiyah Kendari, 2022)
Gunung Traktor area is one of Balikpapan's urban areas which has hilly contours with an average slope of 15% -40% and a height difference of approximately 10-30 meters. Based on these conditions, the community has problems in the process of collecting waste to the TPS. Communities tend to burn garbage communally in their yards rather than throwing garbage into TPS. If these conditions continue to occur, in the long run it will have an impact on environmental pollution because burning waste produces chemicals in the form of carbon monoxide, carbon dioxide, benzene, dioxins, and other harmful substances that will interfere with the respiratory system. In an effort to overcome these problems, it is necessary to know the zoning of garbage collection in Gunung Tractor Area. The purpose of this study is to determine the zoning pattern of garbage collection in Gunung Tractor Area. The mapping analysis method is used to analyze the physical characteristics of Gunung Traktor area through recording and drawing maps using the ArcGIS application, so that the zoning pattern of garbage collection in Gunung Tractor Area can be mapped based on the similarity of the physical characteristics of the area. Based on the results of the analysis, 6 zones of waste collection patterns were obtained, namely zones A, B, C, D, E, and F. In zone D it is recommended to provide TPS RT with the consideration of having the closest access that can be reached by all zones in Gunung Tractor Area